Studi Laju Pengeringan Umbi Porang pada Berbagai Ukuran Umbi dan Periode Panen - Saifuddin Afif; Sri Rahayoe; Eni Harmayani; Fertika Nur Fitriyana; Lisa Astiana Ghina (The University of Lampung, 2026)
Porang (Amorphophallus oncophyllus) is a strategic glucomannan source for food and industrial applications, whose chip and flour quality is strongly influenced by drying performance; however, the combined effects of harvest month and tuber size on convective drying kinetics remain poorly quantified. This study estimated the convective heat transfer coefficient (h) and effective drying rate constant (k) of 7-mm porang slices using a coupled heat–mass balance framework. Tubers were classified into three size categories and dried in a 50 °C cabinet dryer across five harvest months (June–October), with continuous monitoring of air and product temperatures. The Lewis thin-layer model was solved numerically using a fourth-order Runge–Kutta method, and parameters were estimated by minimizing the mean absolute percentage error. Product temperature profiles showed rapid initial heating, a quasi-steady plateau at 43–46 °C, and a final rise, indicating dominance of the falling-rate regime. Estimated h ranged from 42 to 72 W·m⁻²·°C⁻¹ and kₚ from 2.70 to 3.99 h⁻¹. Two-way ANOVA showed no significant effects of harvest month, tuber size, or their interaction (p > 0.05), supporting the use of effective average parameters for robust drying-process standardization and scale-up.